2013
DOI: 10.1007/s00442-013-2615-x
|View full text |Cite
|
Sign up to set email alerts
|

Supply determines demand: influence of partner quality and quantity on the interactions between bats and pitcher plants

Abstract: Interspecific relationships such as mutualism and parasitism are major drivers of biodiversity. Because such interactions often comprise more than two species, ecological studies increasingly focus on complex multispecies systems. However, the spatial heterogeneity of multi-species interactions is often poorly understood. Here, we investigate the unusual interaction of a bat (Kerivoula hardwickii hardwickii) and two pitcher plant species (Nepenthes hemsleyana and N. bicalcarata) whose pitchers serve as roost f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 69 publications
0
31
0
Order By: Relevance
“…The bat droppings enhance the nitrogen intake of N. hemsleyana by 34% on average [10]. In turn, the pitcher plants provide the bats with roosts that are free of parasites, have a stable microclimate, and offer enough roosting space for one or two bats while at the same time preventing the bats from falling into the digestive fluid due to their unique morphological shape and low fluid level [11]. Finding and identifying N. hemsleyana pitchers that grow in the dense Bornean peat swamp forests, however, is a challenging task for echolocating bats: they have to distinguish echoes of the pitchers from those of the cluttered surroundings [13,14].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The bat droppings enhance the nitrogen intake of N. hemsleyana by 34% on average [10]. In turn, the pitcher plants provide the bats with roosts that are free of parasites, have a stable microclimate, and offer enough roosting space for one or two bats while at the same time preventing the bats from falling into the digestive fluid due to their unique morphological shape and low fluid level [11]. Finding and identifying N. hemsleyana pitchers that grow in the dense Bornean peat swamp forests, however, is a challenging task for echolocating bats: they have to distinguish echoes of the pitchers from those of the cluttered surroundings [13,14].…”
Section: Resultsmentioning
confidence: 99%
“…Finding and identifying N. hemsleyana pitchers that grow in the dense Bornean peat swamp forests, however, is a challenging task for echolocating bats: they have to distinguish echoes of the pitchers from those of the cluttered surroundings [13,14]. The situation is further complicated by the fact that the bats need to distinguish the rare [11,15] N. hemsleyana pitchers from the more common and similarly shaped pitchers of sympatric Nepenthes species, which are unsuitable for roosting [10].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As highlighted by , a number of authors have observed or experimentally demonstrated stable ecological, physiological and morphological differences between two subgroups within the taxon N. rafflesiana sensu Danser, comprising different UV reflectance patterns, scent production and capture rate (Moran 1996), the different ontogeny of pitcher morphology (Gaume & Di Giusto 2009), alternative insect trapping strategies (Bauer et al 2011), and a mutualistic interaction with bats exclusive for one subgroup , Schöner et al 2013. Although the two subgroups were clearly understood by all of the specialists, the nomenclature used has been informal and inconsistent, until Independent from all of the work above, N. rafflesiana var.…”
Section: Research Article Introductionmentioning
confidence: 99%
“…All 17 radio-tracked bats followed in Borneo roosted exclusively in pitchers of Nepenthes hemsleyana [4]. The roosting bats in turn increase the nitrogen intake of the plant by a third [8]. Hence, Michael and Caroline Schö ner joined forces with Ralph Simon who had previously measured echo reflectivity in bat-pollinated plants to ask whether pitcher plants have ultrasonic reflectors that might enhance their conspicuousness to echolocating bats.…”
mentioning
confidence: 99%